Rancangan Model Dimensi Kimball Pada Data Warehouse Perusahaan Manufaktur - Fauziyah Fauziyah; Iskandar Zulkarnain; Andy Rio Handoko; Hany Maria Valentine; Dwi Lestari (JOINS (Journal of Information System), 2026)
Modern manufacturing companies face significant challenges from large data volumes and fragmented information systems, which hinder effective data-driven decision-making. This study aims to address these issues by designing a dimensional model for a data warehouse in an electronics manufacturing company, integrating scattered operational data into a single, unified repository. By applying Kimball's Business Dimensional Life Cycle methodology, this study systematically goes through four stages: defining core business processes, declaring data granularity, identifying dimensions, and identifying facts. The result is a fact constellation model (star schema) consisting of 11 grains, 8 fact tables, 8 star schema models, and 1 dimensional model. This proposed model simplifies data access for in-depth analysis, providing a robust and reusable framework to support strategic decision-making in a modern manufacturing environment